Perubahan Spasial Permukiman Sulaa Baubau Pasca Reklamasi Pantai - Ishak Kadir; Achmad Djunaedi (Forum Teknik, 2015)
Sulaa is one of the coastal villages in Baubau, most people work as fishermen and weaver, therefore the sea is a very important part of their lives. Local Government has reclaimed Sulaa coast as an effort to solve abrasion that was faced by Sulaa’s people every year. The reclamation has impact on the social, economic, and cultural community. This paper aims to show the variety of spatial changes of settlements and spatial behavior of people in the postreclamation of the coastal settlement. This research uses Phenomonology paradigm and inductive analysis methods. The main instrument is the researcher ownself with the hypothesis that a researcher can see the object in its context, observes directly and improves the awarness continuously.     This research showed there are spatial changes occured in post-reclamation of the coastal settlement, includes (1) a change in the spatial patterns and density of buildings, which is followed by a change in the orientation of the building and adjustment of space in their homes, especially the buildings in the area of reclamation;(2) spatial patterns of social, economic and cultural community tends to be oriented to the shore.Keywords: Spatial changes, post-reclamation of the coastal settlement, Sulaa.